THE UNCERTAINTY OF LEGAL PROTECTION FOR HOUSEMAIDS IN INDONESIA - Hariri, Achmad; Sahid, Mualimin Mochammad (Kanun Jurnal Ilmu Hukum, 2024)
Several cases of physical, psychological, and sexual violence against housemaids in Indonesia have been documented, despite the existence of laws that aim to protect them. The Law Number 13 of 2003 on the Ministry of Manpower and the Ministry Regulation Number 2 of 2015 on the Protection of Housemaids are insufficient to prevent unfair treatment of housemaids. This study investigates this issue by examining the situation of housemaids in Surabaya, East Java, Indonesia. Using a normative-empirical research approach, this article reveals that legal protection for housemaids in Indonesia is still uncertain due to two primary factors. Firstly, the lack of clarity in the rules requires the development of special laws that specifically address the protection of housemaids. Secondly, the lack of knowledge among housemaids renders them vulnerable to being underestimated and humiliated. The urgency of legal protection for housemaids in Indonesia is underscored by the prevalence of domestic violence and unfair compensation. Therefore, a comprehensive and exhaustive legal framework is necessary to provide a sufficient access to justice mechanisms for housemaids, including legislative acts that are specifically tailored to their needs. Furthermore, rehabilitation is a vital mechanism, particularly for housemaids who have suffered from violence. This can involve providing temporary shelters, counseling, and protection from retaliation.